Basic Approaches and Principles in Teaching Text Structure - Shejauddin Hanif; Mohammad Basir Moqemi (Academia Open, 2026)
General Background: Teaching text structure is a central component of native language education aimed at developing coherent oral and written communication. Specific Background: Methodological and linguistic studies emphasize diverse approaches and principles guiding the extraction of theoretical knowledge, skill formation, and error prevention in text construction. Knowledge Gap: Despite extensive literature, a systematized synthesis of core approaches and principles for teaching text structure remains insufficiently articulated. Aims: This article aims to identify and classify fundamental approaches and principles underlying the teaching of text structure and the development of stable text-building skills. Results: The study delineates key linguistic, cognitive, communicative, modular, and competency-based principles, highlighting their roles in organizing theoretical content and designing effective exercises. Novelty: The article integrates these approaches into a coherent methodological framework grounded in existing theoretical and methodological sources. Implications: The findings support more systematic and principle-based instruction of text structure, contributing to improved communicative competence and speech culture in native language education.Keywords : Text Structure Teaching, Linguistic Pedagogical Approaches, Textual Error Correction, Native Language Instruction, Communicative Competence DevelopmentHighlight : Modular learning technology divides text structure concepts into independent modules for systematic knowledge acquisition. Textual errors include logical, compositional, and grammatical mistakes requiring targeted instructional intervention strategies. Linguistic phenomena demonstrate communicative essence through connected speech requiring integrated systematic native language education.